Purificação e caracterização bioquímica de substâncias bioativas produzidas por endofítico isolado de Prunus spp - Serrano, Nadja Fernanda Gonzaga (Universidade Federal de São Carlos, 2009)
Bioprospective studies of endophytic microorganisms for biotechnological applications are essentials to discovery new substances, which can be used in different areas. Endophytes represent an excellent source of bioactive natural products with chemical structure and biological activities diverses. An endophytic microorganism, isolated from leaves of Prunus spp. (Cerrado of Sao Carlos, SP, Brazil), showed antagonic potential against important pathogen in Public Health. The endophytic microorganism was phenotipic and genetic identified like a Paenibacillus polymyxa and it was given the strain designation RNC-D. The fresh brut extract showed maximum antimicrobial potency of 800 AU.mL-1 against Escherichia coli ATCC 25922 (48 hours of culture) and Staphylococcus aureus ATCC 25923 (120 hours of culture). The bioactive substances contained on extract kept bioactivity after enzymatic assay with proteases and lipase, pH variation from 2.0 to 9.0, thermic treatment using low (-80, - 20 ºC) and high temperatures (100, 121 ºC) against both microorganisms tested. The molecular weight of bioactive substances against E. coli was estimated by ultrafiltration as smaller than 1 kDa, while the bioactive compounds against S. aureus have the molecular weight between 1 and 2 kDa. It was possible to separate the bioactive substances contained in the extract produced by P. polymyxa RNC-D using chromatographic technique (HPLC). Three new molecules, with molecular weight 403, 420 and 425 Da were identified in bioactive peak (eluted in 22% of solution 20 mM TRIS + 1 M NaCl) against E. coli using LC-MS. This research will be continued to determinate the antimicrobial spectrum of the purified molecules, as well as to evaluate the potential application areas.
Keywords: Biotecnologia; Microorganismos endofíticos; Micromoléculas bioativas; Cerrado; Produtos biotecnológicos - purificação; OUTROS